G21 Long-term outcome of pneumococcal haemolytic uraemic syndrome. (12th March 2018) - Waters, A; Dewsnip, A
Abstract : Aims: Haemolytic uraemic syndrome [HUS] is defined by microangiopathic haemolytic anaemia [MAHA], thrombocytopaenia and oliguria/elevated creatinine for age clinically manifesting from endothelial cell injury and microvascular thrombosis. Occurring as a rare complication of pneumococcal infection, P-HUS accounts for 5%–15% of HUS cases in young children and is characterised by a more severe disease course compared to Shiga-toxin associated HUS.¹ We determined the long-term renal outcome of P-HUS¹ and serotype profile of P-HUS following the introduction of the pneumococcal conjugate vaccines (PCV7 and PCV13) in the UK. Methods: A case note review of P-HUS was undertaken in 5 participating UK centres. P-HUS was defined as reported¹ and cases were included if followed for at least 5 years' duration. Data pertaining to duration of dialysis at presentation, duration of follow up, estimated GFR at follow up, proteinuria, blood pressure percentile, dialysis requirement and transplantation was collected. Additional information pertaining to mortality and co-morbidties were also collected. Information on pneumococcal serotype in post 2007 cases [following PCV vaccine introduction in UK] was also collected. Research protocols were approved by regional governance teams. Results: Long-term outcome data was available for 16 of 38 patients who were previously reported¹. All patients presented with P-HUS between April 1999 and February 2010: Median age at presentation: 10 months (IQR:8, 17), M:F 6:10, (0.6). Median duration of hospitalisation: 37 days (IQR:23, 75 days). Median eGFR 54 mls/min/1.73 m² (IQR:25, 81) with median duration of follow-up: 10 years (IQR: 8, 12). At time of follow up, none were on dialysis but three patients [18%] had received renal transplants without recurrence. Nine patients [56%] were on anti-hypertensive treatment at follow up, 7 of whom are on monotherapy [ACEI(5)] and 2 on dual therapy [ACEI with other]. Three patients had persistent proteinuria. Individual data will be presented. Following PCV7 introduction in 2010, the predominant serotype was 3 [previously 19A] and after PCV13 introduction, no cases of P-HUS have been observed since 2012. Conclusion: Over 60% of P-HUS patients under follow-up have chronic kidney disease. Ongoing analysis involving more UK centres is underway including those discharged from care. Reference: . Waters, et al . J Pediatr2007August;151(2):140–4.